Impact of E-Samsat Implementation and BBNKB Elimination on Taxpayer Compliance, with Tax Socialization as a Moderator - Ni Made Mila Dwi Lestari; I Ketut Jati (E-Jurnal Akuntansi, 2026)
Tax compliance remains a persistent issue today, including in Gianyar Regency. This study aims to analyze the effects of implementing e-Samsat and eliminating transfer fees on motor vehicle taxpayer compliance, with tax socialization serving as a moderating variable among taxpayers in Gianyar Regency. The sample comprised 100 respondents selected through accidental sampling. Data collection was conducted using a questionnaire and analyzed with moderated regression analysis in SPSS 26. The results indicated that the implementation of e-Samsat and the elimination of name transfer fees significantly influenced taxpayer compliance. Furthermore, tax socialization effectively moderated the impact of e-Samsat implementation and name transfer fee elimination on taxpayer compliance. This research contributes to attribution theory and provides empirical evidence regarding motor vehicle tax compliance.